The activities of government and self–government institutions in the field of food policy in the Nal-chik district in the last third of the XIX – early XX centuries - Elena A. Anishchenko (Кавказология, 2024)
The article defines the role of government and local government bodies in the sphere of food policy in the Nalchik district of the Terek region in the last third of the 19th – early 20th centuries. Based on various office documentation, the forms of activity of government institutions to control the food situation are considered. The sequence of interaction and responsibility distribution among various national and local government organizations in the implementation of food policy is examined. The process of regular analysis of food prices, as well as their logistics, forage, etc. is considered. The system of controlling the weight of commodities sold through the mandated use of public scales, for which regional and district authorities and local governments split responsibilities, was examined. A conclusion was made about the organizational and control nature of the functionality of district authorities, which was reflected in the formation of a regular statistical and analytical base as annual reports of district heads, which were a form of representation of the state of the national economy and the level of food reserves; and also about the control by government bodies not only of the process of food production but also of their sale through systematic monitoring of food prices and the conditions for carrying out trade operations.